Monomer composition

CN122940940APending Publication Date: 2026-10-20RESONAC CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611117660.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2021-04-19
Publication Date
2026-10-20

AI Technical Summary

Benefits of technology

根据本发明的一方面,提供一种含有金属粉末的多孔质成形体的高温下的机械强度的单体组合物、成形体、粘结磁体及压粉磁芯。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention relates to a monomer composition for inclusion in the pores of a porous molded article. The molded article contains metal powder and a thermosetting resin composition. The monomer composition contains at least one compound selected from the group consisting of acrylates having a dicyclopentane structure, acrylates having a dicyclopentene structure, methacrylates having a dicyclopentane structure, and methacrylates having a dicyclopentene structure.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of Chinese Patent Application No. 202180096741.2, filed on April 19, 2021, entitled "Monomer Composition, Molded Body, Bonded Magnet and Powdered Magnetic Core". Technical Field

[0002] One aspect of the present invention relates to a monomer composition, a molded body, a bonded magnet, and a pressed powder magnetic core. Background Technology

[0003] As a product of powder metallurgy, it is used to manufacture magnetic components or structural parts such as bonded magnets, pressed powder cores, and sintered magnetic cores. In these manufacturing processes, a molded body is formed by shaping metal powder under high pressure. Because voids easily form in the metal powder constituting the molded body, the molded body made of metal powder is porous. Traditionally, to improve the mechanical strength of the molded body and to add additional functions, resin is impregnated into the voids within the molded body.

[0004] For example, the method for manufacturing a metallic material described in Patent Document 1 below includes a step of impregnating resin into the voids of a porous metallic material (sintered body). As a result, a metallic material with excellent vibration damping properties can be obtained. The method for manufacturing a bonded magnet described in Patent Document 2 below includes a step of impregnating epoxy resin and acrylate compounds into the voids of a molded body made of magnetic powder. As a result, the detachment and peeling of magnetic powder in the bonded magnet are suppressed.

[0005] Existing technical documents Patent documents Patent Document 1: Japanese Patent Application Publication No. 2020-85004 Patent Document 2: Japanese Patent Application Publication No. 4-27102 Patent Document 3: Japanese Patent Application Publication No. 2019-48948 Summary of the Invention

[0006] The technical problem to be solved by the invention Molded bodies containing metal powder (such as bonded magnets and pressed powder cores) require environmental resistance (e.g., mechanical strength at high temperatures) depending on their application. In recent years, with increasing demands for environmental resistance, the insufficient mechanical strength of molded bodies due to voids has gradually become a technical challenge. In the case of conventional bonded magnets and pressed powder cores, mechanical strength is imparted to the molded body by mixing a binder such as a thermosetting or thermoplastic resin with metal powder. Furthermore, as mentioned above, to improve the mechanical strength of the molded body, the resin is impregnated within the voids of the molded body.

[0007] The resin needs to be effectively impregnated into the fine pores within the bonded magnet or powder-pressed core. Furthermore, it is desirable for the impregnating resin to impart heat resistance (mechanical strength at high temperatures) to the bonded magnet or powder-pressed core. However, previously, there were no suitable impregnating resins for bonded magnets or powder-pressed cores. For example, when using encapsulating materials such as acrylic resin or polyurethane resin for impregnation, it is difficult for the bonded magnet and powder-pressed core to achieve sufficient heat resistance (mechanical strength at high temperatures).

[0008] One objective of this invention is to provide a monomer composition, a molded body, a bonded magnet, and a pressed powder magnetic core for improving the mechanical strength of porous molded bodies containing metal powder at high temperatures.

[0009] means for solving technical problems The monomer composition involved in one aspect of the present invention is a monomer composition for impregnating the voids in a porous compact. The compact contains metal powder and a thermosetting resin composition. The monomer composition contains at least one compound selected from the group consisting of acrylates having a dicyclopentane structure, acrylates having a dicyclopentene structure, methacrylates having a dicyclopentane structure, and methacrylates having a dicyclopentene structure.

[0010] The monomer composition of one aspect of the present invention may also contain at least one of an acrylate having a glycidyl group and a methacrylate having a glycidyl group.

[0011] The monomer composition involved in one aspect of the present invention may also contain at least one of hydroxyl-containing acrylates and hydroxyl-containing methacrylates.

[0012] Thermosetting resin compositions may contain at least one functional group selected from the group consisting of glycidyl groups, hydroxyl groups, amide groups, and imide groups.

[0013] One aspect of the present invention relates to a molded article comprising metal powder, a thermosetting resin composition, and a resin having at least one of a dicyclopentane structure and a dicyclopentene structure.

[0014] The molded articles according to one aspect of the present invention may also contain acrylic resin having glycidyl groups.

[0015] The molded articles according to one aspect of the present invention may also contain acrylic resin having hydroxyl groups.

[0016] Resins having at least one of the structures of dicyclopentane and dicyclopentene can be acrylic resins.

[0017] Resins having at least one of the structures of dicyclopentane and dicyclopentene may also contain at least one of the functional groups of glycidyl group and hydroxyl group.

[0018] Resins having at least one of the structures of dicyclopentane and dicyclopentene may also have a crosslinked structure containing -CH(OH)-CH2-.

[0019] Resins having at least one of the structures of dicyclopentane and dicyclopentene can be bonded to thermosetting resin compositions via cross-linking structures.

[0020] Metal powder can be a permanent magnet or a soft magnetic material.

[0021] One aspect of the present invention relates to a bonded magnet comprising the above-described molded body, wherein the metal powder contained in the molded body is at least one of Sm-Fe-N magnets and Nd-Fe-B magnets.

[0022] One aspect of the present invention relates to a pressed powder magnetic core comprising the above-mentioned molded body, wherein the metal powder contained in the molded body is at least one of pure iron and iron-containing alloys.

[0023] Invention Effects According to one aspect of the present invention, a monomer composition containing a porous molded body of metal powder with high mechanical strength at high temperature, a molded body, a bonded magnet, and a pressed powder magnetic core are provided. Attached Figure Description

[0024] Figure 1 These are partial schematic diagrams (cross-sectional views) of a porous molded body impregnated with a monomer composition, and partial schematic diagrams (cross-sectional views) of a molded body containing a monomer composition.

[0025] Figure 2 This is a schematic diagram of the thermosetting resin composition 2 (cured product) contained in the molded body.

[0026] Figure 3 A schematic diagram of a resin (polymer of monomer composition) having a dicyclopentane structure, a dicyclopentene structure, a glycidyl group, and a hydroxyl group. Detailed Implementation

[0027] Preferred embodiments of the present invention will now be described with reference to the accompanying drawings. In the drawings, the same reference numerals are used to refer to the same constituent elements. The present invention is not limited to the embodiments described below. "(meth)acrylate" as used herein refers to either acrylate or methacrylate, or both. "(meth)acrylate group" refers to either acrylate or methacryloxy group, or both.

[0028] The monomer composition involved in this embodiment is a monomer composition used for impregnating the pores in a porous molded body. That is, at least part or all of the numerous pores in the molded body are filled with the monomer composition. The monomer composition can be liquid at room temperature. The porous molded body contains metal powder and a thermosetting resin composition. The thermosetting resin composition can be a cured product. The molded body not impregnated with the monomer composition can be formed solely from metal powder and the thermosetting resin composition. Figure 1 The molded body 10A is part of a porous molded body that is not impregnated with monomer composition 4A. Figure 1 The molded body 10B is part of a molded body impregnated with monomer composition 4A. Within each molded body, multiple metal particles 1 constituting the metal powder are bonded together by a thermosetting resin composition 2. Part or all of the surface of each metal particle 1 can be covered by the thermosetting resin composition 2. Multiple pores 3 are formed within the molded body 10A that is not impregnated with monomer composition 4A. These pores 3 can also be referred to as pores. For example, pores 3 can be formed between adjacent metal particles 1. A pore 3 can be a space surrounded by the thermosetting resin composition 2 covering each metal particle 1. Multiple pores 3 can communicate with each other. Each pore 3 formed inside the molded body 10A can communicate with the outside of the molded body 10A through pores 3 opening on the surface of the molded body 10B. Therefore, monomer composition 4A can be impregnated within each pore 3 formed inside the molded body 10A through pores 3 opening on the surface of the molded body 10A. For example, the size (pore diameter) of the pores 3 in the molded body 10A can be smaller than the particle size of the metal powder. For example, the size (pore diameter) of the void 3 in the molded body 10A can be 0.1 μm or more and 100 μm or less. However, the size (pore diameter) of the void 3 in the molded body 10A is not limited.

[0029] Monomer composition 4A contains at least one compound selected from the group consisting of acrylates having a dicyclopentane structure, acrylates having a dicyclopentene structure, methacrylates having a dicyclopentane structure, and methacrylates having a dicyclopentene structure. The dicyclopentane structure is represented by the following chemical formula (1). The dicyclopentene structure is represented by the following chemical formula (2). Monomer composition 4A may contain a variety of (meth)acrylates having a dicyclopentane structure or a dicyclopentane structure. Monomer composition 4A may contain all of the acrylates having a dicyclopentane structure, acrylates having a dicyclopentene structure, methacrylates having a dicyclopentane structure, and methacrylates having a dicyclopentene structure. For ease of description, one or both of the dicyclopentane structure and the dicyclopentene structure are designated as a "cyclic crosslinking structure".

[0030] Monomer composition 4A is polymerized (gelled) by heating. By polymerizing the monomer composition 4A containing the aforementioned (meth)acrylate with a cyclic crosslinking structure, a resin 4B (polymer) with a cyclic crosslinking structure is generated. That is, by heating the molded body 10B, in which monomer composition 4A is impregnated, resin 4B with a cyclic crosslinking structure is generated within each void 3, and each void 3 is filled with resin 4B with a cyclic crosslinking structure. Resin 4B with a cyclic crosslinking structure can be an acrylic resin.

[0031] Compared to other acrylic resins, resin 4B with a cyclic crosslinking structure tends to have a high glass transition point (Tg). Therefore, the molded body 10B containing resin 4B with a cyclic crosslinking structure exhibits excellent heat resistance and high mechanical strength at high temperatures. The mechanical strength of the molded body at high temperatures is, for example, the mechanical strength of the molded body at temperatures above 100°C and below 200°C. The cyclic crosslinking structure itself does not need to react with other functional groups.

[0032] The cyclic cross-linked structure in the molded body 10B can be detected by the following methods.

[0033] The powder obtained by pulverizing the molded body 10B is added to a solvent containing metal powder with a lower specific gravity (true specific gravity) than that in the molded body 10B. As a result, the metal powder settles in the solvent, while the components of the molded body 10B other than the metal powder (resin components) float in the solvent. The cyclic cross-linked structure is detected by analyzing the resin components separated from the metal powder using thermal decomposition gas chromatography / mass analysis. That is, the resin components separated from the metal powder are decomposed into multiple components with small molecular weights by a decomposition device. These multiple components are separated by gas chromatography, and the components (molecules) corresponding to the cyclic cross-linked structure are detected by mass analysis of each separated component.

[0034] (Meth)acrylates having a cyclic cross-linked structure can be at least one (meth)acrylate selected from the group consisting of dicyclopentenyl acrylate (FA-511AS), dicyclopentenyloxyethyl acrylate (FA-512AS), dicyclopentyl acrylate (FA-513AS), dicyclopentenyl methacrylate (FA-511M), dicyclopentenyloxyethyl methacrylate (FA-512MT), and dicyclopentyl methacrylate (FA-513M). The designation in parentheses above indicates the product name manufactured by Showa DenkoMaterials co., Ltd.

[0035] Monomer composition 4A may further contain at least one of glycidyl acrylate and glycidyl methacrylate. Monomer composition 4A may further contain at least one of hydroxyl acrylate and hydroxyl methacrylate. Monomer composition 4A may further contain both glycidyl (meth)acrylate and hydroxyl (meth)acrylate. Resin 4B having a cyclic crosslinked structure may be a copolymer formed from cyclic crosslinked (meth)acrylate and glycidyl (meth)acrylate. Resin 4B having a cyclic crosslinked structure may be a copolymer formed from cyclic crosslinked (meth)acrylate and hydroxyl (meth)acrylate. Resin 4B having a cyclic crosslinked structure may be a copolymer formed from cyclic crosslinked (meth)acrylate, glycidyl (meth)acrylate, and hydroxyl (meth)acrylate.

[0036] Free radical polymerization of monomer composition 4A yields an acrylic resin (crosslinked body) having at least one of glycidyl groups and hydroxyl groups. When monomer composition 4A contains a polyfunctional (meth)acrylate having two or more (meth)acrylate groups, free radical polymerization readily yields an acrylic resin (crosslinked body) having at least one of glycidyl groups and hydroxyl groups. Further heating of the acrylic resin generated by free radical polymerization can induce a crosslinking reaction between the glycidyl groups of the acrylic resin and themselves. Further heating of the acrylic resin generated by free radical polymerization can induce a crosslinking reaction between the glycidyl groups and hydroxyl groups of the acrylic resin. Figure 3 As shown, through the above-described crosslinking reaction, resin 4B with a cyclic crosslinking structure can possess a robust structure composed of acrylic resin 6 interlinked in a mesh-like manner. That is, resin 4B with a cyclic crosslinking structure can also possess a crosslinking structure containing -CH(OH)-CH2- (a crosslinking structure derived from glycidyl groups). As a result, the heat resistance of the molded article 10B is easily improved, and the mechanical strength of the molded article 10B at high temperatures is easily increased.

[0037] Heating an acrylic resin and thermosetting resin composition generated by free radical polymerization allows at least one of the glycidyl groups and hydroxyl groups in the acrylic resin to react with functional groups in the thermosetting resin composition. As a result, a cross-linked structure can be formed between the acrylic resin and the thermosetting resin composition.

[0038] A portion of the glycidyl group in the (meth)acrylate may remain in the molded body 10B without reacting with other functional groups. That is, the molded body 10B may also contain an acrylic resin having a glycidyl group. A portion of the hydroxyl group in the (meth)acrylate may remain in the molded body 10B without reacting with other functional groups. That is, the molded body 10B may also contain an acrylic resin having a hydroxyl group. The resin 4B having a cyclic crosslinked structure may also have at least one of the functional groups selected from glycidyl and hydroxyl groups.

[0039] The (meth)acrylate having a glycidyl group can be, for example, at least one of glycidyl methacrylate and glycidyl acrylate.

[0040] The hydroxyl-containing (meth)acrylate can be, for example, at least one of hydroxyethyl 2-acrylate and hydroxymethyl 2-acrylate.

[0041] Before monomer composition 4A is impregnated into molded body 10A, the thermosetting resin composition 2 in molded body 10A may contain at least one functional group selected from the group consisting of epoxy, glycidyl, hydroxyl, amino, amide, imide, carboxyl, and anhydride (-(C=O)-O-(C=O)-). For example, epoxy and glycidyl groups may be derived from epoxy resins. For example, hydroxyl groups may be derived from at least one of epoxy resins and phenolic resins. Figure 2 As shown, the thermosetting resin composition 2 may be composed of epoxy resin 5 cross-linked in a mesh-like manner, and may also contain unreacted glycidyl groups and hydroxyl groups remaining after cross-linking (thermal curing). For example, the amide groups may be derived from at least one of polyamide resins and polyamide-imide resins. For example, the imide groups may be derived from at least one of polyimide resins, polyamide-imide resins, and bismaleimide resins.

[0042] As monomer composition 4A polymerizes, the glycidyl groups contained in monomer composition 4A or its polymer can react with the aforementioned functional groups contained in thermosetting resin composition 2 to form a cross-linked structure containing -CH(OH)-CH2-. As monomer composition 4A polymerizes, the hydroxyl groups contained in monomer composition 4A or its polymer can react with the glycidyl groups contained in thermosetting resin composition 2 to form a cross-linked structure containing -CH(OH)-CH2-. That is, resin 4B having a cyclic cross-linked structure can be bonded (integrated) with thermosetting resin composition 2 through a cross-linked structure containing -CH(OH)-CH2-. As a result, the heat resistance of molded body 10B is easily improved, and the mechanical strength of molded body 10B at high temperatures is easily increased.

[0043] Since monomer composition 4A is readily impregnated into the voids 3, monomer composition 4A may also contain a low-viscosity (meth)acrylate. For example, the low-viscosity (meth)acrylate may be at least one (meth)acrylate selected from the group consisting of stearyl acrylate, triethylene methoxyacrylate, polyethylene methoxyacrylate (methoxy polyethylene glycol #400 acrylate), tripropylene methoxyacrylate, diethylene phenoxyacrylate, lauryl methacrylate, and benzyl methacrylate (product names manufactured by Showa Denko Materials Co., Ltd.).

[0044] Since cross-linking structures are easily formed during the polymerization of monomer composition 4A, monomer composition 4A may also contain a polyfunctional (meth)acrylate having two or more (meth)acrylate groups. For example, the polyfunctional (meth)acrylate may be at least one (meth)acrylate selected from the group consisting of pentaerythritol tetraacrylate, 1,4-butanediol methacrylate, neopentyl methacrylate, methoxydiethylene glycol dimethacrylate, methoxytetraethylene glycol dimethacrylate, and methoxydiethylene glycol dimethacrylate.

[0045] Because the molded body 10B readily exhibits flexibility, the monomer composition 4A may also contain a (meth)acrylate with a relatively long alkyl chain. For example, the (meth)acrylate with an alkyl chain may be at least one (meth)acrylate selected from the group consisting of lauryl methacrylate and dodecyl methacrylate.

[0046] To polymerize (gel) monomer composition 4A by heating, monomer composition 4A may contain a thermal free radical polymerization initiator. For example, the thermal free radical polymerization initiator may be at least one compound selected from the group consisting of azo compounds and peroxides. Since no gas is generated during the generation of thermal free radicals, the thermal free radical polymerization initiator is preferably an organic peroxide. Organic peroxides dissolved in (meth)acrylate (monomers) can be used. The organic peroxide is preferably liquid at room temperature. For example, the organic peroxide may be at least one compound selected from the group consisting of benzoyl peroxide, tert-butylperoxy-2-ethylhexanoate (PERBUTYL O, the product name manufactured by NOF CORPORATION), and lauryl peroxide.

[0047] For example, monomer composition 4A can be prepared by mixing a (meth)acrylate with a cyclic crosslinking structure, a low-viscosity (meth)acrylate, a multifunctional (meth)acrylate, and a thermal free radical polymerization initiator. The thermal free radical polymerization initiator can be formulated into monomer composition 4A before it is impregnated into molded body 10A.

[0048] The total mass of all (meth)acrylates contained in monomer composition 4A can be expressed as 100 parts by mass, and the mass ratio of the thermal free radical initiator to 100 parts by mass of (meth)acrylates is 0.1 parts by mass or more and 5 parts by mass or less, preferably 1 part by mass or more and 2 parts by mass or less.

[0049] The viscosity of monomer composition 4A can be adjusted according to the composition and mixing ratio of the various (meth)acrylates constituting monomer composition 4A. The viscosity of monomer composition 4A at 25°C is preferably 1 mPa·s or more and 200 mPa·s or less, more preferably 10 mPa·s or more and 100 mPa·s or less, and most preferably 20 mPa·s or more and 90 mPa·s or less. Because monomer composition 4A has such a relatively low viscosity as described above, it can be easily impregnated into the fine pores 3 within the molded body 10A.

[0050] The monomer composition 4A can be impregnated in the voids 3 within the porous molded body 10A using the following method. The porous molded body 10A is entirely impregnated in the monomer composition 4A contained within a container capable of depressurizing its interior. Through subsequent depressurization within the container, the gas filling the voids within the molded body 10A is removed to the outside of the molded body 10A. After the gas is removed from the molded body 10A, the gas pressure within the container is restored to atmospheric pressure. Using the above method, the monomer composition 4A is impregnated in the voids 3 within the porous molded body 10A. The depressurization operation and atmospheric pressure release within the container can be performed once, or the depressurization operation and atmospheric pressure release can be repeated alternately multiple times.

[0051] The first heat treatment of the molded body 10B impregnated with monomer composition 4A can induce thermal polymerization of monomer composition 4A (formation of resin 4B having a cyclic crosslinking structure), crosslinking reaction within resin 4B having a cyclic crosslinking structure, and crosslinking reaction between resin 4B having a cyclic crosslinking structure and thermosetting resin composition 2. The temperature of the first heat treatment of the molded body 10B can be approximately equal to the decomposition temperature of the thermal free radical polymerization initiator in monomer composition 4A. The temperature and required time of the first heat treatment of the molded body 10B vary depending on the composition of the thermal free radical polymerization initiator. For example, the temperature of the first heat treatment of the molded body 10B is 40°C or higher and 120°C or lower, preferably 60°C or higher and 110°C or lower, and more preferably 80°C or higher and 100°C or lower. The required time of the first heat treatment of the molded body 10B is 30 minutes or higher, and preferably 1 hour or higher.

[0052] When monomer composition 4A contains at least one of (meth)acrylate having a glycidyl group and (meth)acrylate having a hydroxyl group, a second heat treatment of the molded body 10B can be performed after the first heat treatment described above. The temperature for the second heat treatment of the molded body 10B is 150°C or higher and 210°C or lower, and can be 180°C or higher and 200°C or lower. The time required for the second heat treatment of the molded body 10B can be 10 minutes or higher and 60 minutes or lower. The mechanical strength of the molded body 10B can be further improved by the second heat treatment of the molded body 10B.

[0053] The impregnation content Rm of monomer composition 4A, as defined by Formula 1 below, can be 0.1% by mass or more and 5.0% by mass or less, or 0.57% by mass or more and 1.3% by mass or less. M in Formula 1... B The mass of the molded body 10B impregnated with monomer composition 4A. M B This can also be referred to as the mass of the molded body 10B containing resin 4B with a cyclic cross-linked structure. M in Formula 1 A The mass of the porous molded body 10A before impregnation with monomer composition 4A. When the impregnation amount of monomer composition 4A is within the above range, the magnetic or soft magnetic properties of the molded body 10B and the mechanical strength of the molded body 10B at high temperatures are easily compatible.

[0054] Rm=(M B -M A )÷M B ×100 (1) The metal powder can be a permanent magnet. For example, a permanent magnet can be a samarium-cobalt (Sm-Co) alloy magnet, a neodymium-iron-boron (Nd-Fe-B) alloy magnet, a samarium-iron-nitrogen (Sm-Fe-N) alloy magnet, an iron-cobalt (Fe-Co) alloy magnet, or an Al-Ni-Co alloy magnet (AlNiCo magnet). When the metal powder is a permanent magnet, the particle size of the magnetic powder can be, for example, 20 μm or more and 300 μm or less, or 40 μm or more and 250 μm or less.

[0055] The bonded magnet involved in this embodiment may be a molded body 10B containing a powder containing a permanent magnet (for example, at least one of Sm-Fe-N magnet and Nd-Fe-B magnet), a thermosetting resin composition 2, and a resin 4B having a cyclic cross-linked structure.

[0056] The metal powder can be a soft magnetic material. For example, the metal powder used as a soft magnetic material can be at least one metal selected from the group consisting of pure iron and iron-containing alloys. The iron-containing alloy can be, for example, at least one metal selected from the group consisting of Fe-Cr alloys (stainless steel), Fe-Ni-Cr alloys (stainless steel), Fe-Si alloys, Fe-Si-Al alloys (iron-silicon-aluminum), Fe-Ni alloys (iron-nickel alloys), Fe-Cu-Ni alloys (iron-nickel alloys), Fe-Co alloys (iron-cobalt alloys), Fe-Cr-Si alloys (electromagnetic stainless steel), and Fe-Ni-Mn-C alloys (Invar). The metal powder used as a soft magnetic material can be amorphous. The metal powder used as a soft magnetic material can be an Fe amorphous alloy. The metal powder used as a soft magnetic material can be at least one of amorphous iron powder and carbonyl iron powder. When the metal powder is a soft magnetic material, the particle size of the metal powder can be, for example, 60 μm or more and 150 μm or less.

[0057] The pressed powder magnetic core involved in this embodiment can be a molded body 10B containing powder of the aforementioned soft magnetic material (e.g., at least one of pure iron and iron-containing alloys), thermosetting resin composition 2, and resin 4B having a cyclic cross-linked structure. The pressed powder magnetic core can be used, for example, in inductors, transformers, reactors, thyristor valves, noise filters (EMI filters), choke coils, motor cores, rotors and yokes of motors in general household appliances and industrial equipment, solenoid cores (fixed cores) for solenoid valves of electronically controlled fuel injection devices assembled in diesel and gasoline engines, position sensors, and magnetostrictive sensors.

[0058] Metal powders can contain a variety of metallic elements. For example, in addition to the elements mentioned above, metal powders can also contain at least one element from the group consisting of base metals, noble metals, transition metals, and rare earth elements. For example, metal powders can also contain at least one element from the group consisting of copper (Cu), titanium (Ti), manganese (Mn), cobalt (Co), nickel (Ni), zinc (Zn), aluminum (Al), tin (Sn), chromium (Cr), barium (Ba), strontium (Sr), lead (Pb), silver (Ag), oxygen (O), beryllium (Be), phosphorus (P), boron (B), and silicon (Si).

[0059] The molded body 10A (molded body 10B) may contain one type of metal powder or multiple types of metal powder. For example, the molded body 10A (molded body 10B) may contain multiple types of metal powder with different average particle size or median particle size (D50). The shape of each metal particle 1 constituting the metal powder is not particularly limited. Each metal particle 1 may be, for example, spherical, flat, or needle-shaped. The particle size of the metal powder can be calculated based on the weight of the metal particles sieved. The particle size of the metal powder can be determined by a laser diffraction particle size distribution measuring device. In addition to the aforementioned metal powder, the molded body 10A (molded body 10B) may also contain inorganic fillers (e.g., silicon dioxide (SiO2) particles).

[0060] Thermosetting resin composition 2 may contain at least one thermosetting resin selected from the group consisting of epoxy resin, phenolic resin, bismaleimide resin, polyimide resin, and polyamide-imide resin. In addition to the aforementioned thermosetting resins, thermosetting resin composition 2 may also contain a polyamide resin (thermoplastic resin). The functional groups contained in the thermosetting resin can react with any one of the glycidyl groups and hydroxyl groups of the resin 4B having a cyclic crosslinking structure to form a crosslinking structure (-CH(OH)-CH2-). For example, at least one thermosetting resin selected from the group consisting of epoxy resin, phenolic resin, bismaleimide resin, polyimide resin, and polyamide-imide resin has at least one functional group consisting of a glycidyl group and a hydroxyl group. The glycidyl group of the thermosetting resin can react with any one of the glycidyl groups and hydroxyl groups of the resin 4B having a cyclic crosslinking structure to form a crosslinking structure (-CH(OH)-CH2-). The hydroxyl groups of the thermosetting resin can react with the glycidyl groups of resin 4B, which has a cyclic crosslinking structure, to form a crosslinked structure (-CH(OH)-CH2-). Due to the crosslinking structure between resin 4B and the thermosetting resin, the mechanical strength of the molded body 10B at high temperatures can be further improved. For the same reason, the functional groups (e.g., amide groups) of the polyamide resin in the thermosetting resin composition 2 can react with the glycidyl groups of resin 4B, which has a cyclic crosslinking structure, to form a crosslinked structure (-CH(OH)-CH2-).

[0061] For example, epoxy resins can be selected from biphenyl-type epoxy resins, stilbene-type epoxy resins, diphenylmethane-type epoxy resins, sulfur-containing epoxy resins, phenolic varnish-type epoxy resins, dicyclopentadiene-type epoxy resins, salicylaldehyde-type epoxy resins, copolymer epoxy resins of naphthols and phenols, epoxides of aralkyl-type phenolic resins, bisphenol-type epoxy resins, glycidyl ether-type epoxy resins of alcohols, glycidyl ether-type epoxy resins of p-xylene and / or m-xylene-modified phenolic resins, glycidyl ether-type epoxy resins of terpene-modified phenolic resins, and cyclopentadiene-type epoxy resins. At least one resin from the group consisting of diene-type epoxy resin, glycidyl ether-type epoxy resin of polycyclic aromatic ring modified phenolic resin, glycidyl ether-type epoxy resin of naphthalene-containing phenolic resin, glycidyl ester-type epoxy resin, glycidyl or methyl glycidyl type epoxy resin, alicyclic epoxy resin, halogenated phenolic varnish-type epoxy resin, o-cresol phenolic varnish-type epoxy resin, hydroquinone-type epoxy resin, thioether-type epoxy resin, trimethylolpropane-type epoxy resin, and linear aliphatic epoxy resin obtained by oxidizing olefin bonds with peracids such as peracetic acid.

[0062] For example, the phenolic resin can be at least one resin selected from the group consisting of arylalkyl phenolic resin, dicyclopentadiene phenolic resin, salicylaldehyde phenolic resin, phenolic varnish phenolic resin, copolymer phenolic resin of benzaldehyde-type phenol and arylalkyl-type phenol, p-xylene and / or m-xylene modified phenolic resin, melamine modified phenolic resin, terpene modified phenolic resin, dicyclopentadiene-type naphthol resin, cyclopentadiene modified phenolic resin, polycyclic aromatic ring modified phenolic resin, biphenyl-type phenolic resin, and triphenylmethane-type phenolic resin. The phenolic resin can be a copolymer composed of two or more of the above-mentioned resins. The phenolic resin can be included as a curing agent together with the epoxy resin in the thermosetting resin composition 2.

[0063] Phenolic varnish resin (phenolic varnish type phenolic resin) can be, for example, a resin obtained by condensation or co-condensation of phenols and / or naphthols and aldehydes under an acidic catalyst. The phenols constituting the phenolic varnish resin can be, for example, at least one selected from the group consisting of phenol, cresol, xylenol, resorcinol, catechol, bisphenol A, bisphenol F, bisphenol, phenylphenol, and aminophenol. The naphthols constituting the phenolic varnish resin can be, for example, at least one selected from the group consisting of α-naphthol, β-naphthol, and dihydroxynaphthalene. The aldehydes constituting the phenolic varnish resin can be, for example, at least one selected from the group consisting of formaldehyde, acetaldehyde, propionaldehyde, benzaldehyde, and salicylaldehyde.

[0064] The phenols constituting phenolic varnish resins can be compounds having two phenolic hydroxyl groups in one molecule. Compounds having two phenolic hydroxyl groups in one molecule can be, for example, at least one selected from the group consisting of resorcinol, catechol, bisphenol A, bisphenol F, and substituted or unsubstituted bisphenols.

[0065] The ratio of the hydroxyl equivalent of the phenolic resin to the epoxy equivalent of the epoxy resin can be 0.5 or more and 1.5 or less, 0.9 or more and 1.4 or less, 1.0 or more and 1.4 or less, or 1.0 or more and 1.2 or less. That is, relative to 1 equivalent of epoxy groups in the epoxy resin, the ratio of the active groups (phenolic OH groups) in the phenolic resin that react with the epoxy groups in the epoxy resin can preferably be 0.5 equivalents or more and 1.5 equivalents or less, more preferably 0.9 equivalents or more and 1.4 equivalents or less, further preferably 1.0 equivalents or more and 1.4 equivalents or less, and particularly preferably 1.0 equivalents or more and 1.2 equivalents or less.

[0066] For example, bismaleimide resins may contain an addition reaction product of maleimide (a) and aminophenol (b), and an epoxy compound (c). The addition reaction product is obtained by reacting maleimide (a) and aminophenol (b), and the bismaleimide resin can be obtained by adding epoxy compound (c) to the addition reaction product.

[0067] The maleimide class (a) constituting the bismaleimide resin is represented by the following chemical formula (A).

[0068] In chemical formula (A), R1 is an n-valent organic group. X1 and X2 are each a monovalent atom or a monovalent organic group selected from hydrogen or halogen. X1 and X2 can be the same, or they can be different from each other. In chemical formula (A), n is an integer greater than 2.

[0069] Maleimide class (a) can be, for example, at least one compound selected from the group consisting of ethylene bismaleimide, hexamethylene bismaleimide, m-phenylene bismaleimide, p-phenylene bismaleimide, 4,4'-diphenylmethane bismaleimide, 4,4'-diphenyl ether bismaleimide, 4,4'-diphenyl sulfone bismaleimide, 4,4'-dicyclohexylmethane bismaleimide, m-xylene bismaleimide, p-xylene bismaleimide, and 4,4'-phenylene bismaleimide. As desired, the above-described maleimide class (a) and monomaleimide class can be included in bismaleimide resins. Monomaleimide class can be, for example, N-3-chlorophenylmaleimide or N-4-nitrophenylmaleimide.

[0070] The aminophenols (b) constituting the bismaleimide resin are represented by the following chemical formula (B).

[0071] In chemical formula (B), R2 is a monovalent atom selected from hydrogen or halogen, or a monovalent organic group. In chemical formula (B), m is an integer from 1 to 5.

[0072] Aminophenols (b) can be at least one compound selected from the group consisting of o-aminophenol, m-aminophenol, p-aminophenol, o-aminocresol, m-aminocresol, p-aminocresol, aminoxylenol, aminochlorophenol, aminobromophenol, aminocatechol, aminoresorcinol, aminobis(hydroxyphenol)propane, and aminooxybenzoic acid.

[0073] The epoxy compound (c) constituting the bismaleimide resin has two or more epoxy groups within its molecule. The epoxy compound (c) can be, for example, at least one compound selected from the group consisting of bisphenol A type epoxy resin, bisphenol F type epoxy resin, phenolic varnish type epoxy resin, glycidyl ester resin of polycarboxylic acid, polyglycidyl ether of polyol, polyurethane modified epoxy resin, fatty acid type polyepoxide formed by epoxidizing an unsaturated compound, alicyclic polyepoxide formed by epoxidizing an unsaturated compound, epoxy resin having heterocyclic rings, epoxy resin having heterocyclic rings, and epoxy resin that has been aminated and glycidized.

[0074] The addition reactant is obtained by the reaction of maleimide (a) and aminophenol (b) described above. The mass ratio of aminophenol (b) to 100 parts by mass of maleimide (a) can be 5 to 40 parts by mass, preferably 10 to 30 parts by mass. The reaction temperature of maleimide (a) and aminophenol (b) can be, for example, 50 to 200°C, preferably 80 to 180°C. The reaction time of maleimide (a) and aminophenol (b) can be appropriately adjusted within the range of several minutes to tens of minutes.

[0075] The content of the above addition reactants in the bismaleimide resin can be 30-80% by mass.

[0076] The bismaleimide resin may be, for example, at least one resin selected from KIR-30, KIR-50 and KIR-100 (these are product names manufactured by KYOCERA Corporation).

[0077] For example, the polyimide resin can be a dehydrated condensation polymer of tetracarboxylic anhydride and 4,4'-bis(3-aminophenoxy)biphenyl. The polyimide resin can be at least one of the following: AURUM PL450C, AURUM PL500A, AURUM PL6200, AURUM PD450L (all manufactured by Mitsui Chemicals, Inc.), SolverPI-5600 (manufactured by Solvar), and THERPLIM (manufactured by Mitsubishi Gas Chemical Company, Inc.).

[0078] For example, the polyamide resin can be at least one of nylon 6 particles obtained from ε-caprolactam and nylon 12 particles obtained from laurolactam. For example, the polyamide resin can be at least one resin selected from the group consisting of: nylon 6 particles (TR-1 and TR-2 manufactured by Toray Industries, Inc.); and nylon 12 particles (SP-500 and SP-10 manufactured by Toray Industries, Inc.). For example, the polyamide-imide resin can be a polyamide-imide resin having a siloxane structure. The polyamide-imide resin may have at least two carboxyl groups at at least one end of the molecular chain. The carboxyl groups of the polyamide-imide resin can react with glycidyl groups contained in monomer composition 4A or its polymer to form a cross-linked structure containing -CH(OH)-CH2-. The polyamide-imide resin can be the polyamide-imide resin described in Japanese Patent Application Publication No. 2019-48948.

[0079] Thermosetting resin composition 2 may contain the various thermosetting resins described above. In addition to the thermosetting resins described above, thermosetting resin composition 2 may also contain other resins (e.g., thermoplastic resins). For example, thermosetting resin composition 2 may also contain at least one other resin selected from the group consisting of polyphenylene sulfide resin, acrylic resin, polyethylene, polypropylene, polystyrene, polyvinyl chloride, polyethylene terephthalate, and silicone resin.

[0080] In addition to the thermosetting resin described above, the thermosetting resin composition 2 may also contain at least one compound selected from the group consisting of curing agents, coupling agents (e.g., silane coupling agents), and additives. Additives may be, for example, at least one compound selected from the group consisting of curing accelerators (curing catalysts), flame retardants, waxes (lubricants), and organic solvents.

[0081] Relative to the total mass (100% by mass) of the metal powder and thermosetting resin composition 2, the content of metal powder in the molded body 10A (molded body 10B) can be 95% by mass or more and 99.5% by mass or less, more preferably 96% by mass or more and 99% by mass or less. When the content of metal powder is within the above range, the magnetic or soft magnetic properties of the molded body 10B and the mechanical strength of the molded body 10B at high temperatures are easily compatible.

[0082] The porous molded body 10A (the molded body 10A prior to the impregnation of monomer composition 4A) can be manufactured by the following method.

[0083] A solution of the thermosetting resin composition can be obtained by dissolving the raw materials of the above-mentioned thermosetting resin composition in an organic solvent. The organic solvent can be, for example, at least one solvent selected from the group consisting of acetone, methyl ethyl ketone, methyl isobutyl ketone, benzene, toluene, and xylene. Metal powder is added to the solution of the thermosetting resin composition, dispersing the metal powder in the solution. The organic solvent is removed from the solution containing the metal powder and the thermosetting resin composition by vacuum distillation and drying. As a result, the surface of each metal particle constituting the metal powder is covered by the thermosetting resin composition, obtaining a composite (powder) containing the metal powder and the thermosetting resin composition. When manufacturing a composite containing inorganic fillers, the inorganic fillers can be added to the solution of the thermosetting resin composition along with the metal powder. The surface of both the metal powder and the inorganic filler can be pre-treated with a coupling agent. Lubricants such as saturated fatty acid salts can be added to the composite.

[0084] In the process of removing organic solvent from a solution containing metal powder and a thermosetting resin composition, an evaporator is preferably used to perform vacuum distillation of the organic solvent at room temperature while stirring the solution. After further drying the solid obtained by vacuum distillation using a vacuum dryer or the like, the solid is appropriately pulverized to obtain the composite. Alternatively, atmospheric distillation can be performed while stirring the solution using a kneader or the like. Heating is not preferred as a method for drying the solid obtained by distillation. The solid can be dried by heating the solid at a temperature below 80°C, preferably below 60°C.

[0085] The above-described method for preparing the composite uses a solvent, but the composite can also be prepared without a solvent. That is, the composite can be prepared by dry mixing without using a solvent. For example, a metal powder and a thermosetting resin composition can be mixed in a sealed container at room temperature and pressure.

[0086] A molded article is obtained by compression molding of the aforementioned composite filled into a mold. The molding pressure can be, for example, 500 MPa or more and 2500 MPa or less, or 700 MPa or more and 2000 MPa or less. The density of the molded article relative to the true density of the metal powder is preferably 75% or more and 90% or less, more preferably 80% or more and 90% or less. When the density of the molded article is within the above range relative to the true density of the metal powder, it is easier to improve the magnetic or soft magnetic properties of the molded article and its mechanical strength at high temperatures.

[0087] By heat treatment of the molded body, the thermosetting resin composition in the molded body can be cured. Since the cured thermosetting resin composition binds the metal particles in the molded body together, a molded body with high mechanical strength can be obtained. The heat treatment temperature of the molded body can be any temperature at which the thermosetting resin composition is fully cured. The heat treatment temperature of the molded body can be, for example, 150°C or higher and 450°C or lower, preferably 200°C or higher and 350°C or lower. The atmosphere for heat treatment can be atmospheric air (preferably dry air) or an inert atmosphere (e.g., nitrogen). To suppress oxidation of the metal powder in the molded body, it is preferable to perform the heat treatment of the molded body in an inert atmosphere. If the heat treatment temperature is too high, the metal powder is easily oxidized due to the trace amounts of oxygen inevitably present in the molded body during manufacturing, and the thermosetting resin composition is easily degraded. Furthermore, to suppress oxidation of the metal powder and deterioration of the thermosetting resin composition, the time for maintaining the above-mentioned heat treatment temperature can be several minutes or more and 4 hours or less, preferably 15 minutes or more and 3 hours or less.

[0088] This invention is not necessarily limited to the embodiments described above. Various modifications can be made to this invention without departing from its spirit, and these modifications are also included in this invention.

[0089] Example The present invention will be described in detail through the following embodiments and comparative examples. The present invention is not limited to the following embodiments.

[0090] (Example 1) The monomer composition of Example 1 was prepared by mixing dicyclopentyl methacrylate (FA-513M, manufactured by Showa Denko Materials Co., Ltd.), glycidyl methacrylate (light Ester G, manufactured by Baseconnect Inc.), hydroxyethyl 2-methacrylate (a product manufactured by Fuji Film Wako Co., Ltd.), dodecyl methacrylate (a product manufactured by Fuji Film Wako Co., Ltd.), pentaerythritol tetraacrylate (EBECRYL 40, manufactured by Daicel Corporation), and tert-butylperoxy-2-ethylhexanoate (PERBUTYL O, manufactured by NOF CORPORATION) in a plastic bottle at room temperature.

[0091] The monomer composition is a liquid at room temperature. The mass of each component constituting the monomer composition is shown in Table 1 below. The glass bottle has a volume of 250 ml.

[0092] The viscosity of the monomer composition in Example 1 was measured at 25°C. Anton Paar MCR301 rheometer was used for the viscosity measurement. The viscosities of the monomer compositions are shown in Table 1 below.

[0093] A porous molded body of Example 1 was prepared by compression molding and heating (curing of the thermosetting resin composition) of a composite containing metal powder and a thermosetting resin composition. Nd-Fe-B alloy powder was used as the metal powder. The Nd-Fe-B alloy powder was MQP-B manufactured by Magnequench International, LLC. The average particle size of the Nd-Fe-B alloy powder was 100 μm. The thermosetting resin composition may contain epoxy resin and phenolic resin. The molded body was annular (cylindrical). The dimensions of the molded body were 25 mm outer diameter × 21 mm inner diameter × 3 mm thickness. The content of metal powder in the molded body is shown in Table 1 below. The content of metal powder in the molded body refers to the mass ratio of the metal powder to the total mass of the metal powder and the thermosetting resin composition.

[0094] The volume of the porous molded body was calculated from its dimensions. The mass of the porous molded body was measured using an electronic balance. The density of the porous molded body was calculated by dividing its mass by its volume. The densities of the porous molded body in Example 1 are shown in Table 1 below.

[0095] The monomer composition is impregnated into the pores of a porous molded body using the following method.

[0096] Before impregnation with the monomer composition, the mass M of the porous molded body was measured. A。 A porous molded body and monomer composition are contained in a stainless steel square container, with the entire porous molded body immersed in the monomer composition. The square container containing the molded body and monomer composition is placed inside a vacuum dryer. The internal pressure of the vacuum dryer is gradually reduced using a vacuum pump. After reducing the pressure inside the vacuum dryer until no bubbles are visible forming from the molded body during depressurization, the vacuum dryer is left to stand for 30 minutes. After 30 minutes, the interior of the vacuum dryer is gradually opened to the atmosphere, and the internal pressure returns to atmospheric pressure within approximately 30 minutes. The molded body is removed from the monomer composition, and the monomer composition adhering to its surface is wiped off. The molded body is placed on a polytetrafluoroethylene (PTFE) sheet. The monomer composition impregnated in the molded body is polymerized by heating the molded body at 90°C for 1 hour in an explosion-proof thermostatic bath. Then, the molded body is further heated at 180°C for 30 minutes. An ESPEC Corp. product is used as the explosion-proof thermostatic bath.

[0097] Using the above method, a molded article of a polymer (an acrylic resin with a cyclic cross-linked structure) containing a monomer composition was obtained. The mass M of the molded article containing the acrylic resin with the cyclic cross-linked structure was determined. B Calculate the impregnation content Rm of the monomer composition as defined by the following formula 1. The impregnation content Rm of the monomer composition of Example 1 is shown in Table 1 below.

[0098] Rm=(M B -M A )÷M B ×100 (1) The ring crush strength of a molded body containing an acrylic resin with a cyclic cross-linked structure was determined using the following method. A universal compression testing machine was used to apply compressive pressure to the side of the molded body in a direction perpendicular to the central axis of the cyclic molded body. The compression pressure was increased, and the compression pressure at which the molded body breaks was measured. The compression pressure at which the molded body breaks is referred to as the ring crush strength (unit: MPa). An AG-10TBR manufactured by SHIMADZU CORPORATION was used as the universal compression testing machine. The speed of the crosshead in the crush strength measurement was 1 mm / min. The ring crush strength in atmospheric conditions at room temperature (25°C) and in atmospheric conditions at 150°C was measured. The ring crush strength of Example 1 is shown in Table 1 below.

[0099] (Examples 2-9 and Comparative Examples 1-5) In the preparation of the monomer composition in Example 4, dicyclopentenyl acrylate (FA-511A manufactured by Showa DenkoMaterials co., Ltd.) was used instead of dicyclopentyl methacrylate (FA-513M).

[0100] In the preparation of the monomer composition in Example 5, dicyclopentenyloxyethyl methacrylate (FA-512MT manufactured by Showa Denko Materials co., Ltd.) was used instead of dicyclopentyl methacrylate (FA-513M).

[0101] In Comparative Examples 1-3, no monomer compositions were prepared.

[0102] In the preparation of the monomer compositions of Comparative Examples 4 and 5, FA-513M, FA-511A, and FA-512MT were not used. That is, the monomer compositions of Comparative Examples 4 and 5 did not contain (meth)acrylates with cyclic crosslinking structures.

[0103] The monomer composition of Comparative Example 4 is a mixture formed from 2-hydroxyethyl methacrylate, methyl methacrylate, dodecyl methacrylate, pentaerythritol tetraacrylate and tert-butylperoxy-2-ethylhexanoate.

[0104] The monomer composition of Comparative Example 5 is a mixture formed from methyl methacrylate, dodecyl methacrylate, pentaerythritol tetraacrylate, and tert-butylperoxy-2-ethylhexanoate. The mass of each component constituting the monomer compositions of Examples 2-9, Comparative Examples 4 and 5 is shown in Table 1 below.

[0105] Except as described above, monomer compositions of Examples 2-9 and Comparative Examples 4 and 5 were prepared using the same method as in Example 1. The viscosity of each monomer composition of Examples 2-9 and Comparative Examples 4 and 5 was measured using the same method as in Example 1. The viscosity of each monomer composition of Examples 2-9 and Comparative Examples 4 and 5 is shown in Table 1 below.

[0106] In the fabrication of the porous molded bodies in Examples 7-9 and Comparative Examples 3 and 5, pure iron powder was used instead of Nd-Fe-B alloy powder as the metal powder. The pure iron powder used was a product manufactured by Höganäs AB (Somaloy 500H). The average particle size of the pure iron powder was 75 μm. The dimensions of the annular molded bodies in Examples 7-9 and Comparative Examples 3 and 5 were 30 mm outer diameter × 20 mm inner diameter × 5 mm thickness.

[0107] The content of metal powder in the porous molded articles of Examples 2-9 and Comparative Examples 1-5 is shown in Table 1 for each example.

[0108] In addition to the items described above, porous molded bodies of Examples 2-9 and Comparative Examples 1-5 were prepared using the same method as in Example 1. The densities of the molded bodies of Examples 2-9 and Comparative Examples 1-5 were measured using the same method as in Example 1. The densities of the porous molded bodies of Examples 2-9 and Comparative Examples 1-5 are shown in Table 1 below.

[0109] Except as described above, molded articles of Examples 2-9 and Comparative Examples 4 and 5 containing the monomer composition were obtained using the same method as in Example 1. The impregnation content Rm of the monomer composition in Examples 2-9 and Comparative Examples 4 and 5 was calculated using the same method as in Example 1. The impregnation content Rm of the monomer composition in Examples 2-9 and Comparative Examples 4 and 5 is shown in Table 1 below. The ring compression strength of the molded articles of Examples 2-9 and Comparative Examples 1-5 was measured using the same method as in Example 1. However, the ring compression strength of the molded articles of Comparative Examples 1-3 refers to the ring compression strength of the porous molded articles without impregnation of the monomer composition. The ring compression strength of the molded articles of Examples 2-9 and Comparative Examples 1-5 is shown in Table 1 below.

[0110] The compositions of the metal powders were compared in Examples 1-6, Comparative Examples 1, 2, and 4. The ring-forming strength at 25°C of Examples 1-6 was higher than that of Comparative Examples 1, 2, and 4 at 25°C. The ring-forming strength at 150°C of Examples 1-6 was higher than that of Comparative Examples 1, 2, and 4 at 150°C.

[0111] The compositions of the metal powders were compared in Examples 7-9 and Comparative Examples 3 and 5. The ring-forming strength at 25°C of Examples 7-9 was higher than that of Comparative Examples 3 and 5 at 25°C. The ring-forming strength at 150°C of Examples 7-9 was higher than that of Comparative Examples 3 and 5 at 150°C.

[0112] Industrial availability For example, the monomer composition involved in one aspect of the present invention is used as a raw material for bonded magnets or pressed powder cores.

[0113] Symbol Explanation 1-Metal particles constituting metal powder, 2-Thermosetting resin composition, 3-Porosity, 4A-Monomer composition, 4B-Resin having a cyclic cross-linked structure (polymer of monomer composition), 10A-Porous molded body, 10B-Molded body impregnated with monomer composition (Molded body containing resin having a cyclic cross-linked structure).

Claims

1. A monomer composition for inclusion in the pores of a porous molded body, wherein, The molded body comprises a metal powder and a thermosetting resin composition. The metal powder is a permanent magnet or a soft magnetic material. The thermosetting resin composition contains at least one functional group selected from the group consisting of glycidyl, hydroxyl, amide, and imide groups. The monomer composition comprises at least one compound selected from the group consisting of acrylates having a dicyclopentane structure, acrylates having a dicyclopentene structure, methacrylates having a dicyclopentane structure, and methacrylates having a dicyclopentene structure. The dicyclopentane structure is represented by the following chemical formula (1). The dicyclopentene structure is represented by the following chemical formula (2). The monomer composition further comprises at least one of hydroxyl-containing acrylates and hydroxyl-containing methacrylates. The hydroxyl groups of at least one of the acrylates and the methacrylates react with the functional groups contained in the thermosetting resin composition. 。 2. A monomer composition for inclusion in the pores of a porous molded body, wherein, The molded body comprises a metal powder and a thermosetting resin composition. The metal powder is a permanent magnet or a soft magnetic material. The thermosetting resin composition contains at least one functional group selected from the group consisting of glycidyl, hydroxyl, amide, and imide groups. The monomer composition comprises at least one compound selected from the group consisting of acrylates having a dicyclopentane structure, acrylates having a dicyclopentene structure, methacrylates having a dicyclopentane structure, and methacrylates having a dicyclopentene structure. The dicyclopentane structure is represented by the following chemical formula (1). The dicyclopentene structure is represented by the following chemical formula (2). The monomer composition further comprises at least one of an acrylate having a glycidyl group and a methacrylate having a glycidyl group. The glycidyl group of at least one of the acrylates and the methacrylates reacts with the functional group contained in the thermosetting resin composition. 。 3. The monomer composition according to claim 2, wherein, The monomer composition further comprises at least one of hydroxyl-containing acrylates and hydroxyl-containing methacrylates.

4. The monomer composition according to claim 3, wherein, The hydroxyl groups of at least one of the acrylates and the methacrylates react with the functional groups contained in the thermosetting resin composition.

Citation Information

Patent Citations

  • Resin magnet and its manufacturing method

    JP1992027102A

  • Compound, cured product and bond magnet

    JP2019048948A

  • Metal damping material

    JP2020085004A